School performance gap between non-immigrant and second-generation immigrant children in Sweden—time trends and contributing factors - Okuyama, Kenta; Lönn, Sara Larsson; Khoshnood, Ardavan M.; Assari, Shervin; Sundquist, Jan; Sundquist, Kristina (Frontiers in Public Health, 2025)
We aimed to investigate the school performance gap and its potential trend from 2010 to 2020 in non-immigrant and second-generation immigrant children in Sweden, whether parental mental disorders and low socioeconomic status contribute to this gap and its trends, and whether the effects of these factors differ by immigration status. We used multiple Swedish population registers, including 829,787 children born 1994–2004. We examined the school performance gap and its trends by the interaction between immigration status and year with linear mixed models. We assessed whether parental mental disorders and socioeconomic status contributed to this gap and its trends, and whether their effects on school performance differ by immigration status. The existing gap was explained by parental mental disorders in addition to parental education and neighborhood socioeconomic status for both males and females. The unadjusted model suggested an increasing trend of the existing gap in school performance by immigration status for both males and females. In the adjusted model, the increasing trend of the gap remained among males and was partially attributed to parental education and neighborhood socioeconomic status. The interaction tests showed that the potential effects of these factors on school performance were smaller among second-generation immigrant children. Efforts to reduce the effects of socioeconomic inequalities and parental mental disorders are warranted in addition to extra support for second-generation immigrant children at schools.